Fine-grained temporal coding of visually-similar categories in the ventral visual pathway and prefrontal cortex - Yang eXu; Yang eXu; Christopher eD'Lauro; Christopher eD'Lauro; John A Pyles; John A Pyles; Robert E. Kass; Robert E. Kass; Robert E. Kass; Michael J Tarr; Michael J Tarr (Frontiers in Psychology, 2013)
Humans are remarkably proficient at categorizing visually-similar objects. To better understand the cortical basis of this categorization process, we used magnetoencephalography (MEG) to record neural activity while participants learned--with feedback--to discriminate two highly-similar, novel visual categories. We hypothesized that although prefrontal regions would mediate early category learning, this role would diminish with increasing category familiarity and that regions within the ventral visual pathway would come to play a more prominent role in encoding category-relevant information as learning progressed. Early in learning we observed some degree of categorical discriminability and predictability in both the prefrontal cortex and the ventral visual pathway. Predictability improved significantly above chance in the ventral visual pathway over the course of learning with the left inferiortemporal and fusiform gyri showing the greatest improvement in predictability between 150-250msec (M200) during category learning. In contrast, there was no comparable increase in discriminability in prefrontal cortex with the only significant post-learning effect being a decrease in predictability in inferior frontal gyrus between 250-350msec (M300). Thus, the ventral visual pathway appears to encode learned visual categories over the long term. At the same time these results add to our understanding of the cortical origins of previously-reported signature temporal components associated with perceptual learning.